Performance Evaluation of 5 GHz IEEE 802.11n WPA2 Laboratory Links - Carvalho, Jose Pacheco de (2019)
The increasing importance of wireless communications, involving electronic devices, has been widely recognized. Performance is a crucial issue, leading to more reliable and efficient communications. Security is also critically important. Laboratory measurements were performed about several performance aspects of Wi-Fi IEEE 802.11n WPA2 5 GHz links. Our study contributes to performance evaluation of this technology, using available equipments (HP V-M200 access points and Linksys WPC600N adapters). New detailed results are presented and discussed, namely at OSI level 4, from TCP and UDP experiments. TCP throughput is measured versus TCP packet length. Jitter and percentage datagram loss are measured versus UDP datagram size. Results are compared for both point-to-point and point-to-multipoint links. Comparisons are also made to corresponding results obtained for Open links. Conclusions are drawn about performance of the links.